The causal relationship between remittances and poverty reduction in developing country: Using a non-stationary dynamic panel data - Makram Gaaliche; Montassar Zayati (Atlantic Review of Economics, 2014)
The aim of this article is to investigate the causal relationship between remittances and poverty reduction for 14 emerging and developing countries over the period 1980 - 2012. We proposed a cointegration analysis, using the method of non-stationary dynamic panel data. Our estimation results reveal that causality nexus of poverty and remittances is bi-directional. We also find that the causal impact of poverty reduction on remittance is stronger than the reverse impact. Indeed, despite of its weak impact on the poverty, remittances should be taken seriously, and this by taking measures by developed countries to facilitate the access of immigrants to their territories. Such an initiative could reduce to some extent the inequalities within developing countries.
Keywords: I32; J15; C51; C01; C23; C33; 330; remittances; poverty; developing countries; cointégration; dynamic panel; causality